2016
DOI: 10.1002/2016jg003403
|View full text |Cite
|
Sign up to set email alerts
|

Microbial consortia controlling biogenic gas formation in the Qaidam Basin of western China

Abstract: Knowledge of what controls the activity of subsurface microbial communities is critical for assessing and managing biogenic methane resources. In this study, 19 formation waters and five gas samples were collected at depths of 800 to 1900 m from Quaternary biogenic gas fields of the Qaidam Basin, China. The formation waters were brines with chloride (Cl) concentrations from 1200 to 2700 mM. Bacterial 16S rRNA gene copies ranged from 3.75 × 104 to 2.23 × 106 copies mL−1 of water, and those of archaea ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Combined with above carbon isotope values (− 54.6‰ to − 29.4‰), it can be confirmed that the natural gas was mainly derived from thermal degradation, at low-maturity stage to maturity stage. Compared with intensive negative 13 C 1 shifts in the Quaternary biogenic gas in the eastern Qaidam Basin (− 72.3 to − 60.53‰ 126 , 130 , 131 , few samples from the Yingxiongling Area in the southwest of Qaidam Basin present minor negative drifts. Therefore, the H 2 S-rich natural gas in the southwest of Qaidam Basin was derived from both thermal degradation and biodegradation, with the former of the most importance.…”
Section: Resultsmentioning
confidence: 91%
“…Combined with above carbon isotope values (− 54.6‰ to − 29.4‰), it can be confirmed that the natural gas was mainly derived from thermal degradation, at low-maturity stage to maturity stage. Compared with intensive negative 13 C 1 shifts in the Quaternary biogenic gas in the eastern Qaidam Basin (− 72.3 to − 60.53‰ 126 , 130 , 131 , few samples from the Yingxiongling Area in the southwest of Qaidam Basin present minor negative drifts. Therefore, the H 2 S-rich natural gas in the southwest of Qaidam Basin was derived from both thermal degradation and biodegradation, with the former of the most importance.…”
Section: Resultsmentioning
confidence: 91%
“…The CD‐diagram of the δ 13 C CH4 and δD CH4 signals assigned the methanogenic pathway to CO 2 reduction (Figure 6), consistent with that the calculated fractions of CH 4 were produced by the CO 2 reduction pathway in the sediment core, with an average of 86%. Although salinity, age, and organic substrates are also presumed to be major factors controlling the relative importance of the two methanogenic pathways (Schoell, 1988; Shuai et al., 2016), the contributions of the CO 2 reduction pathway did not show a systemic difference along the depth, where the change of depth referred to the evolution of salinity and sedimentary age of the JC3 sediment core (Table S1 in Supporting Information ), suggesting that the magnitude of these changes did not affect the methanogenic pathway profoundly. A predictable change in the quality of organic matter could be inferred by the changes in sedimentary environments with varying terrestrial input (X.…”
Section: Discussionmentioning
confidence: 99%